Application of Educational Psychology Based on Improved SPBO Optimization Algorithm in English Learning - Peng, Yingying (Frontiers in Psychology, 2022)
It is an inevitable process of current social development to apply the motivational theory of educational psychology in the field of English teaching. The current method is to start with the introduction of new language teaching projects by teachers, and then use excellent training to make students master the knowledge they have learned. The flaw is that such teaching is simplistic in the present. In order to solve these problems, this paper proposes an improved SPOB optimization algorithm, aiming to study the application of motivation theory in educational psychology to current English teaching. By using the formula definition for the excellent and poor students in the improved SPBO optimization algorithm and the criterion function in the cluster analysis, The application process of motivational design model in oral English teaching is explored through the application of SPBO algorithm. And through the investigation and analysis of the experimental process of the application of incentive design model in oral English teaching, the results showed that 77.2% of teachers chose interest incentives, 34.8% of teachers chose cooperation-competition incentives, and 32.6% of teachers chose emotional incentives.